MGAT4A/Galectin9‐Driven N‐Glycosylation Aberration as a Promoting Mechanism for Poor Prognosis of Endometrial Cancer with TP53 Mutation - Zhen Zhu; Jingya Sun; Weiqing Xu; Qinghe Zeng; Hanyi Feng; Lijuan Zang; Yinyan He; Xiao He; Na Sheng; Xuelian Ren; Guobin Liu; He Huang; et al. (Advanced Science)
Abstract Emerging evidence recognizes aberrant glycosylation as the malignant characteristics of cancer cells, but little is known about glycogenes’ roles in endometrial carcinoma (EC), especially the most aggressive subtype carrying TP53 mutations. Using unsupervised hierarchical clustering, an 11‐glycogene cluster is identified to distinguish an EC subtype associated with frequent TP53 mutation and worse prognosis. Among them, MGAT4A (alpha‐1,3‐mannosyl‐glycoprotein 4‐β‐N‐acetylglucosaminyltransferase A) emerges as the most consistently overexpressed glycogene, contributing to EC aggressiveness. In the presence of galectin‐9, MGAT4A increases EC cell proliferation and invasion via promoting glucose metabolism. N‐glycoproteomics further revealed GLUT1, a glucose transporter, as a glycoprotein modified by MGAT4A. Binding of galectin‐9 to the MGAT4A‐branched N‐glycan on GLUT1 enhances its cell membrane distribution, leading to glucose uptake increase. In addition, oncogenic mutations of TP53 gene in EC cells upregulate MGAT4A expression by disrupting the regulatory oversight exerted by wild‐type p53 on tumor‐suppressive miRNAs, including miR‐34a and miR‐449a/b. The findings highlight a new molecular mechanism involving MGAT4A‐regulated N‐glycosylation on the key regulator of glucose metabolism in p53 mutants‐driven EC aggressiveness, which may provide a strategic avenue to combat advanced EC.